Clinical, Bacteriological and Radiological study of severe pneumonia in age group of 2 months to 5 years - Dr. Kirti Mehta; Dr. Vijay Shah; Dr. Ankur Patel; Dr. Dinesh Kalsariya (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Acute respiratory infections (ARI) are one of the commonest causes of death in children in developing countries. The future health of children depends on preventing, diagnosing, treating and limiting Acute Lower Respiratory Tract Infection. The use of these clinical signs in the early detection and treatment of children with pneumonia by primary health care workers forms the basis for the case management strategy formulated by the World Health Organization (WHO) to control mortality and morbidity. Objectives: to study clinical, bacteriological and radiological features of severe pneumonia and to correlate clinical findings with radiological and bacteriological findings. Materials and Method: A prospective observational study among children between 2 months to 5 years of age. A detailed analysis of symptoms and signs such as fever, cough, rapid breathing, refusal of feeds, wheezing, respiratory rate, presence of fever and other signs of cyanosis, etc were noted. Investigations like Hemoglobin, Total WBC count, Differential WBC count, ESR, blood culture Chest X-ray and if require CT scan were done in all patients. Significance for the statistical tests was predetermined at a probability value of 0.05 or less. (p<0.05) Results: over a period of one and half year total 150 cases were included in the study, nearly all patients were presented with cough, tachypnea, fever, chest retractions and other signs. Positive radiological finding were seen in 80.66% of cases.Among bacterial pneumonia, defined radiologicaly; 63.15% had elevated WBC counts; 88.42% had neutrophilia, 67.27% had elevated ESR. Case fatality rate was 6.3% (9 cases). Conclusion: clinical diagnosis by WHO ARI criteria are very sensitive and still can be applied to hospitalized children. Chest X-ray is valuable aid in the diagnosis of pneumonia in children